An Electro-Acoustic Implementation of Tibetan Bowls: Acoustics and Perception. (January 2014) - Aarts, Ronald M.; Ouweltjes, Okke; Bulut, Murtaza
Tibetan singing bowls are employed worldwide for meditation, music, relaxation, personal wellbeing, and religious practices. Each Tibetan bowl can produce a limited number of sounds, defined by the size and material of the bowl, and the actuator device used. Usually, there is a need for a second person to actuate the bowl. Addressing these limitations, we built an electronic device, named eBowl, which can mimic the acoustics of Tibetan bowls, and beyond that, can produce a wide range of other sounds. Furthermore, it can be used for relaxation and sound massage without the need for a second person. The eBowl generates auditory beats that are in EEG alpha frequency range, which can cause brainwave entrainment and lead to relaxation. User tests measuring physiological parameters revealed the eBowl's effectiveness for relaxation, showing that eBowl influences skin conductance, heart rate, and respiration rate and induces relaxation.